Interactions between Biomolecules and Zwitterionic Moieties: A Review - Erfani, Amir; Seaberg, Joshua; Aichele, Clint Philip; Ramsey, Joshua D (Biomacromolecules, 2020)
Throughout the past decade, zwitterionic moieties have gained attention as constituents of biocompatible materials for exhibiting superhydrophilic properties that prevent nonspecific protein adsorption. Researchers have been working to synthesize zwitterionic materials for diverse biomedical applications such as drug delivery, protein stabilization, and surface modification of implantable materials. These zwitterionic materials have been used in assorted architectures, including protein conjugates, surface coatings, nanoparticles, hydrogels, and liposomes. Herein, we summarize recent advancements that further our understanding of interactions between biomolecules and zwitterionic moieties. We focus on the solution behavior of zwitterions and zwitterionic polymers and the molecular interactions between these molecules and biomolecules as determined by both experimental and theoretical studies. Further, we discuss the implications of using such interactions in vivo and how zwitterionic moieties may be incorporated to facilitate targeted delivery of proteins, genes, or small molecules. Finally, we discuss current knowledge gaps that need to be addressed to advance the field.